Kesesuaian individu-organisasi untuk mengurangi keinginan berhenti kerja dengan kompetensi STARA pemimpin sebagai variabel moderasi - Sendy Puspitasari; Amiartuti Kusmaningtyas (Jurnal Manajemen Maranatha, 2025)
The current research focuses on analyzing the influence of person organization fit (P-O fit) on employee turnover intention (ETI) at PT MJI Sidoarjo and investigation of the STARA competence leader's role as a moderator of such effect. This research uses an explanatory causal approach, with saturated sampling techniques in choosing the respondents, amounting to 50. The findings showed a positive relationship between P-O fit with ETI, which goes against the work adjustment theory. Leaders of the STARA competence positively influence ETI and receive the impact of P-O fit on ETI. These findings emphasize the importance of P-O fit management and leadership development in the context of rapid organizational change. This research provides new insights into HR management in the digital era and contributes to the development of strategies to reduce employee turnover and increase operational efficiency and company competitiveness in the Indonesian manufacturing industry.